2022
DOI: 10.1002/cepa.1746
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Studies of Bolted Lap Joints at Elevated Temperature

Abstract: This paper presents an experimental and numerical studies of bolted double lap joints at ambient and elevated temperatures. Nine experiments conducted at the Czech Technical University in Prague investigated the mechanical behavior of bolted lap joints at 20°, 400° and 600°C. The design strengths of steel joints subjected to tensile forces are predicted using European standards for steel structures. The general finite element (FE) software ABAQUS/Standard 6.14 is employed for the numerical analysis. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the study [9], the numerical and experimental study were carried out on bolted lap joints at elevated temperature. The cover and connected plated were fabricated from a single steel plate, grade S355.…”
Section: Bolted Lap Joints In Firementioning
confidence: 99%
See 1 more Smart Citation
“…In the study [9], the numerical and experimental study were carried out on bolted lap joints at elevated temperature. The cover and connected plated were fabricated from a single steel plate, grade S355.…”
Section: Bolted Lap Joints In Firementioning
confidence: 99%
“…Therefore, bolted lap joints and T-stubs in tension were chosen for verification and validation. The experimental results were taken from following studies; bolted lap joint [9] and T-stubs [10] for validation of CBFEM. Individual components are checked according to EN 1993-1-8:2006 [1] and CBFEM results were compared for verification.…”
Section: Verification and Validationmentioning
confidence: 99%
“…The experimental work [11] was performed on 9 double lap joints with two or four bolts positioned perpendicular to the loading direction. The experimental program was performed to measure the resistance of double lap joints at elevated temperature at the Czech Technical University in Prague.…”
Section: Bolted Lap Jointsmentioning
confidence: 99%
“…Wald et al [8] describes that the solid elements are used for generating research-oriented finite element models which are numerical simulation (ROFEM), and the design-oriented finite element models (DOFEM), which can be defined as numerical calculation, include the shell elements. Several studies [9][10][11] indicated that shell elements are reliable models to predict the behaviour of bolted connections at ambient temperatures. Numerical calculations can be used replacing analytical models by engineers in the design level of structural fire engineering.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have carried out tests and finite element studies on columns, beams, joints, and other common components in steel structures under various extreme loads (such as earthquake, corrosion, fire, etc. ), and little research has been conducted at the structural level [2][3][4][5][6][7][8][9][10]. When extreme loads such as earthquakes act on structures (such as long-span steel arch bridges), even if members such as columns and joints are not completely destroyed, the damage caused by excessive relative displacement between members (such as unseating due to damage of restrainers) might still seriously affect the service function of the bridge [11][12][13].…”
Section: Introductionmentioning
confidence: 99%